Performances of upgraded Dwarf-Fayoumi chicken genotype in different feeding systems under smallholder farm management - Ferdaus, AJM; Hassin, BM; Nahar, S; Bhuiyan, MSA; Ali, MS (Bangladesh Journal of Animal Science, 2024)
The experiment was conducted to evaluate the performance of upgraded Dwarf-Fayoumi genotype (IDC♂ × Fay♀) with three different feeding regimes from onset of lay to 72 weeks of age. A total of 90 IDC♂ × Fay♀ birds of third generation (F3) at 16 weeks of age were distributed to 15 selected farmers nearby three villages of Bangladesh Agricultural University, Mymensingh. The villages were Kewatkhali, Boyra and Sutiakhali that selected for intensive, semi-scavenging and scavenging feeding systems, respectively. Each farmer was also given 5 pullets and 1 cockerel. The birds of full feeding and semi-scavenging system were given 76 g and 38 g mash feed per day, respectively. Pullets of semi-scavenging condition were allowed to scavenge in the farmer homesteads. The birds under scavenging condition reared without supplementation and were allowed to scavenge all day long. Result showed a significant difference (p<0.05) among the feeding systems (intensive, semi-scavenging and scavenging) in production and reproduction traits, where intensive full feeding system exerted better performances. However, performance efficiency index (52.24), egg-feed price ratio (2.81) and return over feed cost (4.48) were found to be significantly higher (p<0.001) in semi-scavenging feeding system. The egg weight (p<0.01), breaking strength (p<0.01) and dry yolk weights (p<0.05) were significantly lower in the birds reared under scavenging feeding system, however, these traits were found statistically similar in the birds of intensive and semi-scavenging feeding system. Feeding systems had no impact on survivability of the experimental birds. Taking altogether, it could be concluded that IDC♂ × Fay♀ upgraded chicken under semi-scavenging system performed better than intensive and scavenging system under smallholder farm management. Bangladesh Journal of Animal Science 53 (1): 13-22, 2024